Respuesta :

9514 1404 393

Answer:

  • f^-1(4) = 2
  • f^-1(-5) = -4
  • f^-1(0) = 0

Step-by-step explanation:

The inverse of the function y = f(x) is ...

  x = f^-1(y)

That is, to answer this question, you find the x-value that corresponds to the given y-value. The marked points are ...

  (-4, -5), (-2, -4), (0, 0), (2, 4), (4, 5)

Look for the values 4, -5, 0 as the second number of these ordered pairs, and report the first number of the pair.

  f^-1(4) = 2

  f^-1(-5) = -4

  f^-1(0) = 0